Corps sensibles, corps contraints, corps émancipés : les adolescents face au cinéma - Alice Gallois (Mise au Point)
In a world dominated by the cultural and media industries and faced with a context of transformation in the practices of adolescents (Octobre 2014, Barrère 2011), the role of cultural mediation devices is undergoing an unprecedented reconfiguration, which could be thought through on the basis of reflections arising from this corporeal turn (Jullier, Leveratto 2010) and a new view of youth, admitting "the action proper to the agency of young people (Octobre, Sirota 2013) on cultural objects, devices and institutions" (Dahan, Labadie, Octobre 2014: 41). This is the premise of our research: to examine, from the point of view of adolescents, the postures, perceptions and emotions at play in a film education scheme in order to enable us to rethink mediation practices. Based on a dissertation currently in preparation, this article looks at the many ways in which teenage cinema-goers' physical experience manifests itself in the context of the Lycéens et apprentis au cinéma (LAAC) programme as it is being rolled out in Occitanie.